Mapping cultural heritage in coastal areas with uas: The case study of lesvos island - Papakonstantinou, Apostolos; Kavroudakis, Dimitris; Kourtzellis, Yannis; Chtenellis, Michail; Kopsachilis, Vasilis; Topouzelis, Konstantinos; Vaitis, Michail (My University, 2019)
Dynamic processes in coastal zones and human activities in the coastal environment produce pressure on cultural heritage, especially in touristic places. Unmanned aerial systems (UAS) are used as an additional tool for monitoring cultural heritage sites in sensitive coastal areas. UASs provide low-cost accurate spatial data and high-resolution imagery products in various spatial and temporal scales. The use of UAS for mapping cultural heritage sites in the coastal zone is of increasing interest among scientists and archaeologists in terms of monitoring, documentation, mapping, and restoration. This study outlines the integration of UAS data acquisition and structure from motion (SfM) pipeline for the visualization of selected cultural heritage areas (ancient harbors) in the coastal zone. The UAS-SfM methodology produces very detailed orthophoto maps for mapping and detecting cultural heritage sites. Additionally, a metadata cataloging system has been developed in order to facilitate online searching operations for all products of the data acquisition, SfM pipeline, and cartographic processes. For this reason, a specific metadata profile was implemented, based on the European INSPIRE framework. As a result, datasets reusability and catalogs interoperability are promoted.
Keywords: Cultural heritage areas; Coastal cultural heritage monitoring; UAS; UAV-SfM; Geographic metadata